KONDISI SOSIAL EKONOMI PETERNAK AYAM RAS PEDAGING DI KECAMATAN KOTO TANGAH KOTA PADANG - Wati, Nela - (Pendidikan Geografi, 2014)
This research aims to get data and information about the socio-economic conditions of broiler breeder InKoto Tangah Padang city seen from the formal and non-formal education, the health condition of the breeders,breeder capital and income breeders. Profile breeder chickens ras meaning about the real picture that looks atchicken breeder, i.e. any circumstance that occurs after the rancher is aiming at a chicken farm, anything rancher byproblems due to the chicken farm, as well as the changes that happen to a good chicken breeders in the areas ofeducation, social and economic.Type of this research is descriptive research. The population of this research is the whole broiler breeders in districtof Koto Tangah Padang city. Research samples taken with the dwarf total sampling so that a sample of 51 dairyfarmers. Data collection with question form of misguided social interactions.The research results showed that: 1) formal education broiler breeders: Graduate School and informal educationbroiler breeder does not exist, 2) Codition of broiler breederâs health is generally good, and the type of disease thathas ever suffered by a breeder that is a heasache (56,86%) where medical teratment when sick breeders inMidwife/Mantri and costs derived from the medical treatment at their own expense (58,83) 3) capital of broilerbreeder in purchasing seeds, chicken coops and making other infrastructure large enough Rp. 20,000,000 â50,000,000 (50,98%), the capital source of broiler breeder loans relatives. (%) of 37,25 4 basic income) broilerbreeder is high enough Rp. 2,000,000-5,000,000 (45,10%) and a side income ranges between Rp. 50,000 to 75,000